2022
DOI: 10.1002/pat.5610
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of polybenzimidazole‐based mixed matrix membranes containingmodified‐COK‐12 mesoporous silica and evaluation of the mixed‐gas separation performance

Abstract: This work reports the preparation and characterization of mixed matrix membranes (MMMs) based on mesoporous ordered COK‐12 silica modified with 3‐aminopropyltrimethoxysilane as filler, and a series of polybenzimidazoles with different main‐chain structure as polymer matrix. Polybenzimidazoles (PBIs) were prepared from 3,3′‐diaminobenzidine and several dicarboxylic acids with different chemical structure. The physicochemical studies, as well as thermal, structural, and morphological properties of MMMs were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
(115 reference statements)
0
4
0
Order By: Relevance
“…After water uptake, the residual water from the sample's surface was removed with absorption paper. The water uptake of the membranes was then recorded and calculated using Equation (7).…”
Section: Relation To Membrane Thickness Predictionmentioning
confidence: 99%
See 2 more Smart Citations
“…After water uptake, the residual water from the sample's surface was removed with absorption paper. The water uptake of the membranes was then recorded and calculated using Equation (7).…”
Section: Relation To Membrane Thickness Predictionmentioning
confidence: 99%
“…Polymeric membranes such as phosphonated poly (benzimidazole) can be used in PEMFCs as electrolytes for proton conductivity. [4][5][6][7][8] The casting method can be employed to produce poly (benzimidazole) membranes for studies on PEMFCs. 9,10 Molecular weight of the polymer, 11,12 type of solvent, solution concentration, 13 mold size, drying temperature, 9 and crosslinking [14][15][16][17] are important parameters in the production of membranes suitable for PEMFCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a number of other groups have utilized COK-12 for different purposes. [47][48][49][50][51][52] COK-12 is an excellent candidate for incorporation into a functional AM monolith. Previous work has studied the influence of sintering methods, and found that compaction followed by conventional sintering preserves some mesoporosity and that spark plasma sintering achieved higher mechanical strength.…”
mentioning
confidence: 99%